Analysis of first-year and old ice ridge characteristics - Sudom, Denise; Timco, Garry; Sand, Björnar; Fransson, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2011)
A study has been carried out on the morphological characteristics of arctic and subarctic iceridges, with an emphasis on the differences between first-year and second- or multi-year iceridges. This work builds on the catalogue of ridge shapes created by Timco and Burden in 1995.Sail height, keel depth, and total ridge thickness are investigated, focussing on the differencesbetween first-year and old ridges, and considering the effect of grounding. The consolidated layerthickness and width and overall dimensions of ridges are also examined. Comparisons are madefor arctic and temperate ridges. The arctic regions include the Barents and Norwegian Seas, andthe Beaufort Sea and Canadian/American Arctic. Temperate regions include the Baltic Sea, Gulfof Bothnia, Gulf of Finland, Bering Sea, Sea of Okhotsk, Labrador Coast, and CanadianMaritimes. Relationships between sail height and keel depth are developed, and the findings ofthis study are evaluated against existing statistics and formulae. Godkänd; 2011; Bibliografisk uppgift: Artikel nr POAC 11-164; 20121116 (ysko)